RETRACTED: Level of application of advanced technologies for transformation into intelligent systems of enterprises in the regions - Starodubova Anna; Iskhakova Dinara (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001